Mitochondrial Genome of Prasinophyte Alga Pyramimonas parkeae. (24th October 2016) - Hrdá, Štěpánka; Hroudová, Miluše; Vlček, Čestmír; Hampl, Vladimír
Abstract: Prasinophytes are a paraphyletic assemblage of nine heterogeneous lineages in the Chlorophyta clade of Archaeplastida. Until now, seven complete mitochondrial genomes have been sequenced from four prasinophyte lineages. Here, we report the mitochondrial genome of Pyramimonas parkeae, the first representative of the prasinophyte clade I. The circular‐mapping molecule is 43, 294 bp long, AT rich (68.8%), very compact and it comprises two 6, 671 bp long inverted repeat regions. The gene content is slightly smaller than the gene‐richest prasinophyte mitochondrial genomes. The single identified intron is located in the cytochrome c oxidase subunit 1 gene ( cox1 ). Interestingly, two exons of cox1 are encoded on the same strand of DNA in the reverse order and the mature mRNA is formed by trans‐splicing. The phylogenetic analysis using the data set of 6, 037 positions assembled from 34 mtDNA‐encoded proteins of 48 green algae and plants is not in compliance with the branching order of prasinophyte clades revealed on the basis of 18S rRNA genes and cpDNA‐encoded proteins. However, the phylogenetic analyses based on all three genomic elements support the sister position of prasinophyte clades Pyramimonadales and Mamiellales.